The role of the neighborhood, family and peers regarding Colombian adolescents’ social context and aggressive behavior (2014)
Objective Examining neighborhood conditions, parenting and peer affiliations’ association with adolescents’ aggressive behavior. Testing various mechanisms through which neighborhood conditions influence two adolescent outcomes, both directly and indirectly (via their impact on parenting and peer-affiliation): aggression and delinquency. Method Data regarding adolescents was taken from a self-reporting survey of 1,686 Colombian adolescents living in 103 neighborhoods of Medellin. Neighborhoodrelated data was taken from official government datasets, as well as two separate community surveys. Both multilevel modeling and multilevel structural equation modeling were used in the analysis. Results The probability of an adolescent engaging in aggression in Medellin was 7.0 % and becoming involved in delinquency 0.3 %. There was also significant variation for both forms of aggressive behavior at neighborhood-level (7.0 % aggression and 14 % regarding the delinquency scale). No neighborhood condition had a direct association with adolescents’ aggressive behavior; however; the neighborhood exerted an indirect influence on adolescent behavior which was mainly transmitted through families and the quality of friends within a particular community. Conclusions Residing in disadvantaged neighborhoods did have an adverse effect on adolescents’ aggressive behavior, mainly because of a lack of effective parenting strategies thereby facilitating affiliations being made with deviant peers. More efficient intervention for reducing adolescents’ aggressive behavior should thus target areas having high odds of aggressive behavior and focus on improving community resources and, more importantly, on controlling adolescent peer groups, the lack of parental monitoring and inconsistent discipline.